IMPLEMENTATION OF THE OPEN SELECTION POLICY FOR PRIMARY HIGH LEADERSHIP POSITIONS WITHIN THE PONTIANAK CITY GOVERNMENT - Margaretha Margaretha (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2023)
This study aimed to describe and analyze the implementation of the open selection for the pratama high leadership positions in the Environment of the Pontianak City Government. This study applied Charles O. Jones' policy implementation process theory, which included three (three) components: organization, interpretation, and application. This study also employed the qualitative method in conjunction with a descriptive research design. The results of this study showed that the process of implementing the open selection policy for the pratama high leadership positions in the Environment of Pontianak City Government had been going well, but there were still some obstacles. This was reflected in the analysis of organizational aspects, interpretation, and application. In terms of organization, the implementation process was supported by a qualified organizational structure and human resources, as well as an activity budget allocation large enough to cover all open selection costs except the cost of mental health tests, which is charged to each open selection participant. In terms of interpretation, the implementation process had not been supported by revised mayoral regulations in accordance with the new laws and regulations, but the socialization of the open selection policy to the selection participants had gone well, despite the fact that there were still selection requirements that were unclear to the selected participants. In terms of application, the implementation process had been carried out in accordance with the established requirements and procedures. Keywords: Policy Implementation, Open Selection, Pratama High Leadership Position